Complement Factor H in cSCC: Evidence of a Link Between Sun Exposure and Immunosuppression in Skin Cancer Progression - Johnson, Ellise M.; Uppalapati, Chandana K.; Pascual, Agnes S.; Estrada, Sarah I.; Averitte, Richard L.; Leyva, Kathryn J.; Hull, Elizabeth E. (Frontiers in Oncology, 2022)
Cutaneous Squamous Cell Carcinoma (cSCC) is a common form of skin cancer with an estimated 750,000 cases diagnosed annually in the United States. Most cases are successfully treated with a simple excision procedure, but ~5% of cases metastasize and have a 5-year survival rate of 35-50%. Thus, identification of biomarkers correlated to cSCC progression may be useful in the early identification of high-risk cSCC and in the development of new therapeutic strategies. This work investigates the role of complement factor H (CFH) in the development of cSCC. CFH is a regulatory component of the complement cascade which affects cell mediated immune responses and increases in complement proteins are associated with poor outcomes in multiple cancer types. We provide evidence that sun exposure may increase levels of CFH, suggesting an immunomodulatory role for CFH early in the development of cSCC. We then document increased levels of CFH in cSCC samples, compared to adjacent normal tissue (ANT) routinely excised in a dermatology clinic which, in paired samples, received the same level of sun exposure. We also provide evidence that levels of CFH are even greater in more advanced cases of cSCC. To provide a potential link between CFH and immune modulation, we assessed immune system function by measuring interferon-gamma (IFN-γ) and FOXP3 in patient samples. IFN-γ levels were unchanged in cSCC relative to ANT which is consistent with an ineffective cell-mediated immune response. FOXP3 was used to assess prevalence of regulatory T cells within the tissues, indicating either a derailed or inhibitory immune response. Our data suggest that FOXP3 levels are higher in cSCC than in ANT. Our current working model is that increased CFH downstream of sun exposure is an early event in the development of cSCC as it interferes with proper immune surveillance and decreases the effectiveness of the immune response, and creates a more immunosuppressive environment, thus promoting cSCC progression.